Pengembangan Media Monopoli Puisi untuk Meningkatkan Kemampuan Menulis Puisi pada Siswa Kelas IV SD Negeri Karangsuno - Tsania, Alvina Nafis; Kurnianto, Bagas (Universitas Nusantara PGRI Kediri, 2025)
The purpose of this study was to improve students' poetry writing skills, through the development of appropriate and effective learning media in the form of Monopoly Poetry media. This study applies the ADDIE R&D model method. The subjects of the study included 26 students and teachers of grade IV at SD Negeri Karangsuno, material validators, and media validators. The results of the feasibility test carried out by the material validator obtained a percentage of 90% and from the media validator obtained a percentage of 84%, both of which were included in the